Biscuits enriched with the edible powder of Angoumois grain moth (Sitotroga cerealella): Optimization, characterization and consumer perception assessment - S. M. Mohsen; A. Ashraf; S. S. Ahmed; T. G. Abedelmaksoud (Пищевые системы)
During this study, the dried powder of Angoumois grain moth (Sitotroga cerealella) (AGM) was used as an excellent source of protein to produce nutritional biscuits. Physical, chemical, rheological and microbiological characteristics of biscuits with the optimum AGM percentage (5%) were evaluated compared to the control. The response surface methodology (RSM) with optimal (custom) design was first employed for optimizing the percentage of the AGM powder in biscuits. The optimum selected percentage of the AGM powder was 5% and a quadratic model was found to yield the best fit. The evaluation of parameters of biscuits (ash, protein, fiber and fat content) showed that most of the values, except carbohydrate, significantly increased with AGM inclusion (5%) compared to the control. Also, an increase in diameter, spread ratio and weight values and a decrease in the thickness and break strength of the biscuits were observed with AGM powder inclusion. The presence of the 5% AGM powder slightly increased water absorption, and dough development time also increased compared to the control sample. However, stability of dough decreased. The sanitary conditions of the AGM biscuits were satisfactory as the analytical results were within the established values specified in the regulation. The study revealed that Angoumois grain moth is an excellent source of nutrients necessary for combating protein-energy-malnutrition rampant in our world today.